PP139 Adapting Health Technology Assessment And Procurement To Tackle Antimicrobial Resistance. (2019) - Neri, Margherita; Towse, Adrian; Hampson, Grace; Henshall, Christopher
Abstract : Introduction: The rise of antimicrobial resistance (AMR) as an international public health threat calls urgently for improved stewardship of antibiotics and for the development of new antibiotics to tackle AMR. There is growing agreement that changes are needed to existing systems for health technology assessment (HTA) and procurement if antibiotics are to be used appropriately, and manufacturers are to receive rewards that incentivize research and development. However, there has been little discussion of what changes might actually be made. Methods: We conducted a literature review of recent proposals to modify HTA and contracting for antibiotics, and interviewed HTA experts from England, France, Germany, Italy, Japan, and Sweden to explore the attractiveness of these and other proposals in their countries. A forum (held in February 2019) with government and health system representatives from these countries, as well as from industry, will promote face-to-face discussions on practical ways to modify approaches in these countries to recognize the full value of antibiotics and promote responsible stewardship. Results: The focus of the main proposal is to define value attributes that reflect the societal impact of antibiotics, model the dynamics of infection transmission and resistance development, and conceptualize payment models that delink volumes sold from final revenues. However, HTA experts perceived a number of issues with these proposals, including a lack of data to demonstrate societal value, complex modeling techniques that require advanced capabilities, uncertain value estimates, and lack of alignment with current approaches. At present, it appears that only England and Sweden have started to actively address HTA and contracting for antibiotics as a priority. Conclusions: Preliminary findings suggested that efforts and progress on modifying HTA and contracting of antibiotics have been heterogeneous so far. The forum will shed further light on possible ways forward within the two value assessment approaches of clinical added benefit and quality-adjusted life years.